Proof by Induction: Arithmetic Sum

In summary, the conversation discusses a problem involving the use of induction in a proof. The proposition P(m) is introduced, and the summation equation is used to simplify the equation. The inductive assumption P(k) is then used to prove the result for P(k+1), but there is difficulty in simplifying the numerator into the required form. Suggestions are made to expand and factor the expression to proceed with the proof.
  • #1
sleepingMantis
25
5
Homework Statement
Prove for any ## 1 \leq m < n## that: $$ \sum_{i = m + 1}^{n} i = \frac{(n - m)(n + m + 1)}{2} $$
Relevant Equations
$$ \sum_{1}^{n} i = \frac{n (n + 1)}{2} $$
Hi,

I am self studying induction and came across the following problem. I am stuck on how to proceed (I need to use induction, I know there is a direct proof). My proof attempt is as follows:

Let ## P (m) ## be the proposition that:

$$ \sum_{i = m + 1}^{n} i = \frac{(n - m)(n + m + 1)}{2} $$

Then ## P (1) ## gives:

$$ \sum_{i = 1 + 1}^{n} i = 2 + 3 + ... + n $$

Using the summation equation:

$$ \sum_{i = 2}^{n} i = \frac{n(n + 1)}{2} - 1 $$

$$ \Longleftrightarrow \sum_{i = 2}^{n} i = \frac{n^2 + n - 2}{2} $$

$$ \Longleftrightarrow \sum_{i = 2}^{n} i = \frac{(n - 1)(n + 1 + 1)}{2} $$

Therefore ## P(1) ## is true.

Now assume ## P(k) ## is true such that:

$$ \sum_{i = k + 1}^{n} i = \frac{(n - k)(n + k + 1)}{2} $$

Then ## P(k + 1) ## gives:

$$ \sum_{i = (k + 1) + 1}^{n} i = \sum_{i = (k + 1)}^{n} i - 1 $$

Looking at the right hand side of the equality and using ## P(k) ## :

$$ \frac{(n - k)(n + k + 1)}{2} - 1 $$

This simplifies down to:

$$ \frac{n^2 + n - k^2 - k - 2}{2} $$

My question is how do I proceed from here?

Are there any tricks I should be aware of to convert the numerator into the required form?

Any help is much appreciated!
 
Physics news on Phys.org
  • #2
Usually you would use the assumption of P(k) to prove the result holds for P(k+1) i
sleepingMantis said:
n∑i=(k+1)+1i=n∑i=(k+1)i−1
Sub in the expression for P(k) on the left to the right and verify that P(k+1) holds, i.e., you get what you are supposed to get under the hypothesis, for P(k+1).
 
  • Like
Likes sleepingMantis
  • #3
sleepingMantis said:
Hi,

I am self studying induction and came across the following problem. I am stuck on how to proceed (I need to use induction, I know there is a direct proof). My proof attempt is as follows:

Let ## P (m) ## be the proposition that:

$$ \sum_{i = m + 1}^{n} i = \frac{(n - m)(n + m + 1)}{2} $$

Then ## P (1) ## gives:

$$ \sum_{i = 1 + 1}^{n} i = 2 + 3 + ... + n $$

Using the summation equation:

$$ \sum_{i = 2}^{n} i = \frac{n(n + 1)}{2} - 1 $$

$$ \Longleftrightarrow \sum_{i = 2}^{n} i = \frac{n^2 + n - 2}{2} $$

$$ \Longleftrightarrow \sum_{i = 2}^{n} i = \frac{(n - 1)(n + 1 + 1)}{2} $$

Therefore ## P(1) ## is true.

Now assume ## P(k) ## is true such that:

$$ \sum_{i = k + 1}^{n} i = \frac{(n - k)(n + k + 1)}{2} $$

Then ## P(k + 1) ## gives:

$$ \sum_{i = (k + 1) + 1}^{n} i = \sum_{i = (k + 1)}^{n} i - 1 $$

You said " Then ## P(k + 1) ## gives:

$$ \sum_{i = (k + 1) + 1}^{n} i = \sum_{i = (k + 1)}^{n} i - 1 $$

Stop right there: that is false. You should have
$$\sum_{i=(k+1)+1}^n i = \sum_{i=k+1}^n i - \sum_{i=k+1}^{k+1} i,$$ and that last term is not equal to ##-1.##
 
  • Like
Likes sleepingMantis
  • #4
Ray Vickson said:
You said " Then ## P(k + 1) ## gives:

$$ \sum_{i = (k + 1) + 1}^{n} i = \sum_{i = (k + 1)}^{n} i - 1 $$

Stop right there: that is false. You should have
$$\sum_{i=(k+1)+1}^n i = \sum_{i=k+1}^n i - \sum_{i=k+1}^{k+1} i,$$ and that last term is not equal to ##-1.##

Thanks Ray, I see my mistake (d'oh)

I now instead have:

$$ \sum_{i = (k + 1) + 1}^{n} i = \sum_{i = (k + 1)}^{n} i - (k+1) $$

Applying the inductive assumption ## P (k) ## and simplifying I get:

$$ \frac{n^2 + n - (k^2 + 3k + 2)}{2} $$

But I am not sure how to proceed from here. I thought about applying the quadratic formula to the numerator, but that gives me:

$$ n = \frac{-1 \pm \sqrt{1 + 4(k^2 + 3k + 2)}}{2} \quad (1)$$

Am I even on the right track here?
 
Last edited:
  • #5
sleepingMantis said:
Applying the inductive assumption ## P (k) ## and simplifying I get:

$$ \frac{n^2 + n - (k^2 + 3k + 2)}{2} $$
You have ##P(k) = \frac{(n - k)(n + k + 1)}{2}##. What do you expect to get for ##P(k + 1)##? The numerator should be the product of two trinomials. It's not easy to factor a polynomial into the product of trinomials, but if you expand what ##P(k + 1)## should be, you will see that it is equal to what you have just above.
 
  • Like
Likes sleepingMantis
  • #6
Mark44 said:
You have ##P(k) = \frac{(n - k)(n + k + 1)}{2}##. What do you expect to get for ##P(k + 1)##? The numerator should be the product of two trinomials. It's not easy to factor a polynomial into the product of trinomials, but if you expand what ##P(k + 1)## should be, you will see that it is equal to what you have just above.
Ah this is a much better approach. I was trying to factor, which I cannot seem to figure out how to do.

I guess to complete the proof:

By ## P(K + 1) ## I expected:

$$ \frac {(n - (k+1))(n + (k+1) + 2)}{2} $$

Expanding and simplifying this becomes:

$$ \frac{n^2 + n - k^2 - 3k -2}{2} $$

But this is the same as:

$$ \sum_{i = (k + 1) + 1}^{n} i $$

Hence ## P(k + 1) ## is also true.
 
  • #7
sleepingMantis said:
Hi,

I am self studying induction and came across the following problem. I am stuck on how to proceed (I need to use induction, I know there is a direct proof). My proof attempt is as follows:

Let ## P (m) ## be the proposition that:

$$ \sum_{i = m + 1}^{n} i = \frac{(n - m)(n + m + 1)}{2} $$

Then ## P (1) ## gives:
$$ \sum_{i = 1 + 1}^{n} i = 2 + 3 + ... + n $$
Using the summation equation:
$$ \sum_{i = 2}^{n} i = \frac{n(n + 1)}{2} - 1 $$ ...

Are there any tricks I should be aware of to convert the numerator into the required form?

Any help is much appreciated!
You have completed your inductive task by "counting upwards", starting with m = 1 as the Base case.

I suggest you try the induction by "counting downwards" instead. Use P(n − 1) as the base case, then show that P(k) implies P(k − 1) .

I think you may find that the algebra is less difficult. Beyond that, there is no need to use the summation equation:
##\displaystyle \sum_{i = 1}^{n} i = \frac{n(n + 1)}{2} ##​
.
 
  • Like
Likes sleepingMantis
  • #8
SammyS said:
You have completed your inductive task by "counting upwards", starting with m = 1 as the Base case.

I suggest you try the induction by "counting downwards" instead. Use P(n − 1) as the base case, then show that P(k) implies P(k − 1) .

I think you may find that the algebra is less difficult. Beyond that, there is no need to use the summation equation:
##\displaystyle \sum_{i = 1}^{n} i = \frac{n(n + 1)}{2} ##​
.

Thanks, this is a very interesting approach. I could not factor the numerator in the way I did it.

So the strategy is to use ## P(n-1) ## as a base case, where ##n## can be any arbitrary value?
 
  • #9
sleepingMantis said:
Thanks, this is a very interesting approach. I could not factor the numerator in the way I did it.

So the strategy is to use ## P(n-1) ## as a base case, where ##n## can be any arbitrary value?
Yes.

So P(n − 1) is the proposition that the following statement is true.
##\displaystyle \sum_{i = (n-1) + 1}^{n} { i } \ \ = \frac{(n - (n-1))(n + (n-1) + 1)}{2} ##​

That's easily verified.
 
  • Like
Likes sleepingMantis
  • #10
SammyS said:
Yes.

So P(n − 1) is the proposition that the following statement is true.
##\displaystyle \sum_{i = (n-1) + 1}^{n} { i } \ \ = \frac{(n - (n-1))(n + (n-1) + 1)}{2} ##​

That's easily verified.

Thank you that makes a lot of sense - I will try to employ this new approach as it is very handy!
 

1. What is proof by induction?

Proof by induction is a mathematical method used to prove that a statement holds true for all natural numbers. It involves breaking the statement down into smaller cases and proving that it holds true for the first case (usually n = 1), and then showing that if it holds true for some arbitrary case n, it also holds true for the next case (n+1).

2. How is proof by induction used to prove arithmetic sums?

To prove an arithmetic sum using induction, we first show that the statement holds true for the first case (usually n = 1). Then, we assume that the statement holds true for some arbitrary case n. Using this assumption, we can show that the statement also holds true for the next case (n+1). Finally, we can conclude that the statement holds true for all natural numbers by the principle of mathematical induction.

3. What is the principle of mathematical induction?

The principle of mathematical induction states that if a statement is true for the first case (usually n = 1) and if it is also true for the next case (n+1) whenever it is true for some arbitrary case n, then the statement is true for all natural numbers.

4. Why is proof by induction considered a valid method of proof?

Proof by induction is considered a valid method of proof because it follows a logical and systematic approach. It starts by proving the statement for the first case, and then uses this as a basis to show that it holds true for the next case. This process is repeated until it can be concluded that the statement holds true for all natural numbers.

5. What are some common mistakes to avoid when using proof by induction?

Some common mistakes to avoid when using proof by induction include assuming that the statement is true for all natural numbers without proving it for the first case, assuming that the statement is true for an arbitrary case without proving it for the next case, and using circular reasoning. It is important to carefully follow the steps of proof by induction and clearly explain each step to avoid these mistakes.

Similar threads

  • Precalculus Mathematics Homework Help
Replies
10
Views
2K
  • Precalculus Mathematics Homework Help
Replies
7
Views
966
  • Precalculus Mathematics Homework Help
Replies
10
Views
799
  • Precalculus Mathematics Homework Help
Replies
13
Views
1K
  • Precalculus Mathematics Homework Help
Replies
2
Views
932
  • Precalculus Mathematics Homework Help
Replies
13
Views
1K
  • Precalculus Mathematics Homework Help
Replies
1
Views
1K
  • Precalculus Mathematics Homework Help
Replies
5
Views
575
  • Precalculus Mathematics Homework Help
Replies
4
Views
2K
  • Precalculus Mathematics Homework Help
Replies
14
Views
2K
Back
Top